2019
DOI: 10.1080/15592324.2019.1596718
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a glycogenin, CmGLG2, enhances floridean starch accumulation in the red algaCyanidioschyzon merolae

Abstract: Microalgae accumulate energy-reserved molecules, such as triacylglycerol and carbohydrates, which are suitable feedstocks for renewable energies such as biodiesel and bioethanol. However, the molecular mechanisms behind the microalgae accumulating these molecules require further elucidation. Recently, we have reported that the target of rapamycin (TOR)-signaling is a major pathway to regulate floridean starch synthesis by changing the phosphorylation status of CmGLG1, a glycogenin generally required for the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Most of the proteins involved in starch initiation in plants seem to be absent in these groups. Interestingly, it has been suggested that glycogenin‐like proteins are present in the red alga Cyanidioschyzon merolae (Pancha et al ., 2019), but more work is needed to show that the initiation of Floridean starch formation is similar to the initiation of glycogen formation.…”
Section: Evolutionary Conservation Of the Starch Granule Formation Initiation Mechanismmentioning
confidence: 99%
“…Most of the proteins involved in starch initiation in plants seem to be absent in these groups. Interestingly, it has been suggested that glycogenin‐like proteins are present in the red alga Cyanidioschyzon merolae (Pancha et al ., 2019), but more work is needed to show that the initiation of Floridean starch formation is similar to the initiation of glycogen formation.…”
Section: Evolutionary Conservation Of the Starch Granule Formation Initiation Mechanismmentioning
confidence: 99%
“…Regulation proteins such as TFs, TRs, as well as those involved in post-translational modification, are representing the most promising targets for rewiring carbon partitioning for enhancing production of starches or lipids in microalgae. Recently, the target of rapamycin signaling pathway was found to be involved in starch accumulation via mediating phosphorylation of a glycogenin-like protein (CmGLG1) in the unicellular red alga Cyanidioschyzon merolea , and overexpression of CmGLG1 resulted in 4.7-fold increase in the starch content ( Pancha et al, 2019a ; Pancha et al, 2019b ). An earlier study showed knocking out a Zn (II) 2 Cys 6 gene improved partitioning of the total carbon to lipid from 20 to 40–55% in Nannochloropsis ( Ajjawi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Homologs of glycogen synthase (27) and glycogen phosphorylase (28) regulate the accumulation of amylopectin in this parasite, and TgGat1 has been annotated as a glycogenin (28,29). Related genes have been implicated in promoting starch formation in red algae (30,31). Thus, Gat1 might have a function in regulating T. gondii amylopectin formation.…”
Section: Gat1 Is Closely Related To Glycogeninmentioning
confidence: 99%